2013
DOI: 10.1371/annotation/cedbee08-9c0e-42e3-862f-df7409c273ef
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Contribution of Pannexin1 to Experimental Autoimmune Encephalomyelitis

Abstract: Pannexin1 (Panx1) is a plasma membrane channel permeable to relatively large molecules, such as ATP. In the central nervous system (CNS) Panx1 is found in neurons and glia and in the immune system in macrophages and T-cells. We tested the hypothesis that Panx1-mediated ATP release contributes to expression of Experimental Autoimmune Encephalomyelitis (EAE), an animal model for multiple sclerosis, using wild-type (WT) and Panx1 knockout (KO) mice. Panx1 KO mice displayed a delayed onset of clinical signs of EAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…BBG decreased astrogliosis in the forebrain of immunized rats and alleviated the neurological symptoms. In view of the reported preferential localization of Panx-1 channels in astrocytes and their confirmed role in the release of the potentially neurotoxic ATP [145], it was interesting to observe that Panx-1 KO mice displayed a delayed onset of clinical signs of EAE and decreased mortality compared to wt mice [205].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…BBG decreased astrogliosis in the forebrain of immunized rats and alleviated the neurological symptoms. In view of the reported preferential localization of Panx-1 channels in astrocytes and their confirmed role in the release of the potentially neurotoxic ATP [145], it was interesting to observe that Panx-1 KO mice displayed a delayed onset of clinical signs of EAE and decreased mortality compared to wt mice [205].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…This increase in receptor expression likely compensates for the decrease in ATP release observed in Panx1 KO mice and contributes to the development of EAE symptoms in these mice. This study demonstrates that a Panx1dependent mechanism involving ATP release and/or inflammasome activation plays a role in disease progression, and inhibiting Panx1 through pharmacological means or genetic disruption delays and mitigates the clinical signs of EAE [41].…”
Section: Eae In Pannexin1 Deficient Micementioning
confidence: 74%
“…In the CNS, Panx1 is found in neurons and glial cells, and in the immune system, it is present in macrophages and T cells [40]. Lutz et al conducted a study to test the hypothesis that Panx1-mediated ATP release contributes to the development of EAE, using both wild-type (WT) and Panx1 KO mice [41]. The results showed that Panx1 KO mice exhibited a delayed onset of clinical signs of EAE and a reduced mortality rate compared to WT mice, although they developed comparable clinical severities to the WT mice.…”
Section: Eae In Pannexin1 Deficient Micementioning
confidence: 99%
“…Cdc42. ITGB2, SRF and ERM family (ezrin/radixin/moesin) [46][47][48][49] (iv) Genes that enhance immune cells infiltration of endothelial cells in both paracellular and transcellular routes such as Panx1 [50,51]. (v) Genes that play different roles in paracellular and transcellular routes and these genes include LSP1 which is an endothelial F-actin binding protein, and it moves from the nucleus to the cytosol and is associated with the cytoskeleton on stimulation and the formation of the dome structures [52].…”
Section: Resultsmentioning
confidence: 99%